Synergistic Analysis of Hydrothermally Synthesized PANI-GO: MnO2/MoO3 Nanocomposites for Enhanced Structural and Supercapacitor Performance - R, Kalpana; P, Subbramaniyan (International Research Journal of Multidisciplinary Technovation, 2024)
This study explores the potential of PANI-GO:MnO2/MoO3 nanocomposites as high-performance supercapacitors, addressing the increasing energy storage demands in portable electronics devices. By varying the amount of polyaniline (PANI) alongside a ternary composite of GO/MnO2/MoO3, the present study investigates their combined influence on electrochemical performance. XRD analysis confirmed the hexagonal phase with an average particle size of 19 nm, and FTIR analysis showed the functional groups associated with the title compound. FESEM images demonstrated the leaf-like structures, and the EDAX spectrum confirmed the presence of Mn and Mo elements in the as-prepared samples. Electrochemical analysis showed a maximum capacitance of 596 F/g. The unique blend of graphene, polyaniline, and ternary metal oxides in these nanocomposites holds great promise for advanced supercapacitors. The research aims to understand how different levels of polyaniline impact the overall composition, providing insights into the synergies between these components and their effects on energy storage capabilities.